Intracranial hemorrhage from moyamoya disease during pregnancy and puerperium. Issue 2 (28th January 2014) - Liu, Xing‐Ju; Zhang, Dong; Wang, Shuo; Zhao, Yuan‐li; Ye, Xun; Rong, Wang; Yong, Cao; Kang, Shuai; Zhao, Ji‐Zong
Abstract: Objective: To determine the incidence of hemorrhage among women with moyamoya disease (MMD) during pregnancy and puerperium. Methods: Data were assessed from patients with MMD who were referred to Beijing Tiantan Hospital between January 1985 and December 2012. Women aged 18–40 years with known parturient status were included. Annual hemorrhage rates were calculated as the ratio of number of bleeds to total number of patient‐years of follow‐up. Results: There were 184 patients with MMD. Ninety‐six women were 18–40 years, and 81 had known parturient status. Among the 184 patients, 203 hemorrhages occurred during 5642 patient‐years of follow‐up. The annual hemorrhage rate was 3.6% overall, and 3.9% among 96 female patients ( P > 0.05). Among the 81 patients with known parturient status, 4 hemorrhages occurred during pregnancy and puerperium among 144 pregnancies (hemorrhage rate, 2.8% per pregnancy; 3.2% per year). Among the remaining 77 patients, 86 hemorrhages occurred during 2574 patient‐years of follow‐up (annual hemorrhage rate, 3.3%). The risk of hemorrhage from MMD was not increased during pregnancy and puerperium (hazard ratio, 0.73; 95% confidence interval, 0.23–2.35; P = 0.60). Conclusion: Pregnancy and puerperium are not risk factors for intracranial hemorrhage in hemorrhagic MMD. There is no need to advise patients against pregnancy.